Spectres of Phantasmagoria: Recreation and Analysis of the Soundscape of Robertson's Spectacle (International Journal on Stereo & Immersive Media, 2025)
In the late 18th and early 19th centuries, a specific entertainment show was conquering Europe: the Phantasmagoria. One of its most prominent authors was Étienne-Gaspard Robertson. This paper examines Robertson’s highly frequented rendition at the Convent des Capucines in Paris, maps his inventions and novelties in the show, and, by focusing on the sound elements, creatively reimagines the soundscape of this precinematic experience. Methodologically, the study combines a close reading of period accounts with a creative digital reinterpretation of the Phantasmagoria’s sound environment, employing historically informed sound design and spatial modelling to replicate its auditory effects. The resulting analysis suggests that sound functioned not simply as atmospheric accompaniment but as a central mechanism through which the spectacle shaped spectators’ perceptions, emotions, and beliefs.